Predictive accuracy of lactate albumin ratio for mortality in intensive care units: a nationwide cohort study - Yohei Okada; Yoshitaka Aoki; Mikio Nakajima; Yasuhito Suzuki; Mikihiro Shimizu; Ryo Imai; Soichiro Mimuro; Yoshiki Nakajima (BMJ Open)
Background The lactate albumin ratio (LAR), a simple prognostic marker used in intensive care units (ICUs), combines lactate and serum albumin levels to predict patient outcomes. Despite its potential, the predictive accuracy of the LAR remains insufficiently explored. This study aimed to assess the usefulness of the LAR in predicting mortality among patients in the ICU.Methods This retrospective study conducted a secondary analysis of prospectively obtained clinical data from the Japanese Intensive Care Patient Database. We included all patients admitted to ICUs between 2015 and 2021, excluding those under the age of 16 years. The main outcome was in-hospital mortality. The LAR predictive value for this outcome was assessed by examining the area under the receiver operating characteristic curve and comparing it against prognostic indicators such as age, lactate, albumin and Sequential Organ Failure Assessment score. LAR shape was assessed using unrestricted spline curves, and the optimal cut-off value was identified from sensitivity and negative likelihood ratio. Subgroup analysis was used to evaluate the predictive accuracy of the LAR across different patient attributes and clinical scenarios.Results Of 2 34 774 cases analysed, in-hospital mortality was 8.8% (20 723 deaths). The LAR had an area under the curve of 0.761 (95%CI 0.757 to 0.765), indicating a fair predictive performance for in-hospital mortality. Unrestricted spline curves demonstrated that LAR can predict mortality through a monotonic positive dose–response relationship with 0.4 as the optimal cut-off value. In subgroup analysis, areas under the curve were significantly higher in subgroups defined by younger age, female sex, unplanned ICU admission, non-surgical patients, non-infectious patients, non-heart failure patients and lack of end-stage renal disease.Conclusions The LAR might be a useful predictor for screening mortality in ICU patients. However, further research to establish appropriate cut-off values for the LAR and identify the optimal target population is warranted.